Teresa, Giacinta i Helena – włoskie siostry Emmy, czyli „Pani Bovary” Gustave’a Flauberta w literaturze włoskiej XIX wieku - Krasnopolska, Zuzanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
Through a comparative study, the author tries to outline the differences and similarities between Madame Bovary and three 19th century Italian novels by De Roberto, Verga and Capuana along with an intertextual game the writers engage in with the French original. By a close analysis of the protagonists’ childhood, marriage/adultery, literary education and psychological disorders, the author argues that whilst Emma Bovary falls victim of her illusions, and Elena with Giacinta are only partially Mesdames Bovary, Teresa comes to realise the male power of novels.